Marketing for beginners: step - by - step guide - Othman, Azrina; Mohamad, Norhidayah; Mohd Din, Adilah (Penerbit UTeM Press, 2023)
The university has launched a "Marketing for Beginners: Step by Step Guide" module for Gen Z students at Malaysian Institutions of Higher Learning. The module provides comprehensive information on marketing concepts, theories, and processes, with in-class activities, examples, case studies, and exercises. It combines theory and practice, emphasizing practical execution of marketing techniques and the 4Ps framework.